2017
DOI: 10.1038/s41598-017-11976-6
|View full text |Cite
|
Sign up to set email alerts
|

CXCL6 is an important paracrine factor in the pro-angiogenic human cardiac progenitor-like cell secretome

Abstract: Studies in recent years have established that the principal effects in cardiac cell therapy are associated with paracrine/autocrine factors. We combined several complementary techniques to define human cardiac progenitor cell (CPC) secretome constituted by 914 proteins/genes; 51% of these are associated with the exosomal compartment. To define the set of proteins specifically or highly differentially secreted by CPC, we compared human mesenchymal stem cells and dermal fibroblasts; the study defined a group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 62 publications
6
60
0
Order By: Relevance
“…CXCL6 is described as being an angiogenic chemokine secreted by CPCs [21]. In order to access if the I/R conditioned medium has a pro-angiogenic paracrine profile, the in vitro tube formation assay was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL6 is described as being an angiogenic chemokine secreted by CPCs [21]. In order to access if the I/R conditioned medium has a pro-angiogenic paracrine profile, the in vitro tube formation assay was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The hCPCs employed in this work are not the same population involved in this controversy and were isolated and cultured using a different protocol (Patent WO2014141220A1), which was also used for the isolation of the hCPC population recently evaluated for the allogeneic treatment of AMI in CAREMI clinical trial (NCT02439398). Importantly, these cells were already extensively characterized at the immunomodulatory [1417], total proteome [18], membrane proteome [19, 20], and secretome [21] levels. The regenerative benefit of these cells was studied in vivo in pig AMI animal model [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…CXCL5 is secreted by endothelial cells in response to infection to recruit neutrophils (32). CXCL5 (33) and CXCL6 (34) are shown to have important paracrine functions, including regulation of gene expression and signaling for cell migration and angiogenesis. Our results confirm previous studies that the proteome of ISF is distinct from that of plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the latest report has revealed that majority (≈90%) of the resident c-kit + cells in the rodent heart are blood/endothelial lineage-committed cells, while cardiac c-kit + (blood/endothelial lineage-negative) cells represent ≤ 10% of the total c-kit + cells in the heart [ 29 ]. It is speculated that the positive effects seen from the delivered c-kit + cells in the post-MI setting could be due to the release of signaling molecules, rather than the engrafted cells themselves [ 30 , 31 ].…”
Section: Embryonic and Adult Cardiac Progenitor Cellsmentioning
confidence: 99%